(untitled) (Current Horticulture, 2024)
An experiment was conducted at Banaras Hindu University, Varanasi, Uttar Pradesh, to find the effect of soil application of zinc sulphate and corm size on growth and corm parameters in gladiolus cv. Malaviya Kundan during 2018-19. The experiment was laid out in randomized block design replicated 4 times where mother corms of seven different sizes and zinc sulphate at three different levels were used. The largest-sized corm (4.0 cm) was found to be the best in growth characters like leaf length, scape width and number of leaves/plant. Application of zinc at various doses also provided positive response in days to sprouting and leaf length. Bigger- sized corms (3.0-4.0 cm) produced more no. of corms and cormels/hill, increased diameter and weight of corms compared to small size of mother corms (1.0-2.5 cm). All the doses of zinc sulphate failed to exert any significant effect on production of corms and cormels.